2017
DOI: 10.7592/fejf2017.67.sarv
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Typology of Parallelism in Estonian Poetic Folklore

Abstract: Abstract:The article gives an overview of the uses and features of parallelism across different genres of Estonian poetic folklore, focusing on the genres in which grammatical parallelism forms an important means for structuring texts. Relying on her own previous research on runosongs and short forms of folklore (Sarv 1999(Sarv , 2000(Sarv , 2003, the results of the syntactic analysis of runosong texts in Helle Metslang's dissertation (1978), Juhan Peegel's definition of poetical synonyms in runosongs (Peegel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(On oral Kalevala-meter, see e.g., Sarv 2015; It is usually said that the Kalevala-meter has no rhyme or does not build on rhyme, but the parallelism (e.g., repeating the content of a line in subsequent lines with new wordings) o en creates irregular sections of morphological or grammatical rhyme, as the Finnic languages are rich in morphological variation at the word endings, and the parallel verses o en make use of similar morphological forms. (On parallelism in Kalevala-meter, see Oras 2010;Sarv 2017;Frog & Tarkka 2017;Kallio 2017a.) Yet, the irregular end rhyme relating to parallelism is evidently one aesthetic component of the meter.…”
Section: Kalevala-meter and Grammatical Rhymementioning
confidence: 99%
“…(On oral Kalevala-meter, see e.g., Sarv 2015; It is usually said that the Kalevala-meter has no rhyme or does not build on rhyme, but the parallelism (e.g., repeating the content of a line in subsequent lines with new wordings) o en creates irregular sections of morphological or grammatical rhyme, as the Finnic languages are rich in morphological variation at the word endings, and the parallel verses o en make use of similar morphological forms. (On parallelism in Kalevala-meter, see Oras 2010;Sarv 2017;Frog & Tarkka 2017;Kallio 2017a.) Yet, the irregular end rhyme relating to parallelism is evidently one aesthetic component of the meter.…”
Section: Kalevala-meter and Grammatical Rhymementioning
confidence: 99%
“…Several previous studies [7], [8], [9], [10], [11] have suggested that parallelism can be divided into three types, or species according to Lowth's term, with reference to the division made by Robert Lowth [12], namely synonymous parallelism, antithetic parallelism, and synthetic parallelism. The three types of parallelism are briefly explained as follows:…”
Section: Types Of Parallelismmentioning
confidence: 99%
“…When considering the works of Cajanus and Juslenius, their comparisons may seem like an outgrowth of discussions of biblical parallelism. However, in 4 An exception is Mari Sarv (2017), who recently reframed the background of Porthan's term for parallelism on the basis of De poësi Fennica rather than Steinitz's review (cf. also Frog with Tarkka 2017, 215;Frog 2017, 426n7).…”
Section: Porthan's Intellectual Genealogy In Parallelism Researchmentioning
confidence: 99%